Management of business record / Suriani Jack ... [et.al.] - Jane, Aerica; Adni, Azra Hannani; Nasuha, Nurun; Chundang, Rachel Cindy
This chapters in book is mainly focusing on how business records management functions and the applications of social media in organizations. All articles that are included in this e-publication are taken from research papers that have been done from 2011 to 2022. All of these articles are in the scope of “Social Media Engagement: is it a Need or a Want in Business Records Management”.